The Influence of Job Satisfaction and Organizational Commitment on Employee Turnover Intention Radar Kediri - Anggraini, Fitria Dedek; Swasti, Ika Korika (East Asian Journal of Multidisciplinary Research, 2024)
Business competition means that companies must understand that human resources are assets that must be maintained in which employees have a big role and contribute to the companies operational activities. However, in reality, maintaining a workforce is not easy, turnover is a coomon phenomenon in the business environment. Factors that can influence turnover are job satisfaction and organizational commitment. This problem also occurs in Radar Kediri. The employee turnover rate at this company is quite high, namely 34,4% in 2020. The aim of this research is to examine how the level of job satisfaction and organizational commitment influences employee turnover at Radar Kediri. This research uses quantitative methods which is processed using Smart PLS software version 4. The population in this research is all Radar Kediri employee, totaling 53 and a sample of 53 respondents determined using the saturated sampling method. The analysis techniques are Sem PLS and bootstrapping. The result of this study indicate that job satisfaction and organizational commitment have a negative effect on turnover intention.